Increasing returns to scale, productivity and economic growth – a spatial analysis of the contemporary EU economy - Olejnik, Alicja; Olejnik, Jakub (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2019)
This paper is an attempt to explain variations across 261 regions of 27 EU countries in productivity growth for 2000-2013. The study is based on Fingleton’s model which analyses the spatial process of productivity growth based on some elements of the theory of New Economic Geography and Endogenous Growth Theory. The applied specification links the productivity growth to the growth of output by means of Verdoorn’s law. The model has been tested using the Spatial Panel Durbin Model with Multiple-Level Spatial Fixed Effects. Our findings suggest that increasing returns to scale are present in the EU economy. Moreover, the effect of increasing returns to scale is considerably stronger than has been suggested by both classic and recent research papers. Furthermore, we also find that there are evident spatial clusters of spatial productivity in the EU
Argumenta Oeconomica, 2019, Nr 1 (42), s. 273-293
Keywords: increasing returns to scale; productivity growth; Verdoorn's law; spatial panel